ANALISIS EKONOMI BUDIDAYA PETANI TANAMAN HORTIKULTURA DI KECAMATAN BENGKAYANG - B01107068, MULIONO MUMUL (Jurnal Pembangunan dan Pemerataan, 2013)
The purpose of this study was to determine the economic potential created by or resulting from the cultivation of horticultural crops in the district Bengkayang, to determine the level of earned income of farmers, and to determine the factors inhibiting the cultivation of horticultural crops in the district Bengkayang. The research method used in this research is descriptive method that describes the circumstances and events based on facts and data are available in the District Bengkayang. By using analysis of total revenue or income to determine the income level of farmers and analysis of R / C ratio to determine the profitability of farmers cultivated plants, by using primary data and secondary data from the Central Bureau of Statistics, Department of Agriculture Bengkayang. From the research that has been conducted by the authors, it can be concluded that the economic potential created or produced are potentially increase agricultural community, tinggkat highest net income earned per person in a corn crop of Rp, 1,122,500, - with total revenue Rp13.980.000, - and the constraints faced by farmers in the cultivation of horticultural crops in the district are Bengkayang. Uncertain climate, price is not fixed, and inadequate infrastructure.